Manajemen Promosi Perpustakaan di Kantor Arsip, Perpustakaan, dan Dokumentasi Kota Padang - Sofianida, Sofianida; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
Data were collected through observation and interviews. The findings of the study are (1) The library Pemko Padang has done campaign management library though not running optimally. Media campaigns are used by officers Library Pemko Padang is through the name and logo of agencies, mobile libraries, service on holidays, distribution of brochures, billboards, and a storytelling contest. (2) Obstacles encountered in conducting the campaign management library in the Records Office, the limited budget, the library promotional activities Pemko Padang is not done regularly, the lack of human resources, lack of facilities and infrastructure, lack of library collections. (3) How that should be done by the Library Pemko Padang in overcoming the obstacles faced are: set a budget, or a set period of time in the implementation of library promotion, to increase human resources, infrastructure additions, to increase library collection. Keywords: promotion management; library promotion